Romanticism and the human sciences : poetry, population, and the discourse of the species - McLane, Maureen N. (Cambridge [England] ; New York : Cambridge University Press, 2000)
"This study examines the dialogue between British Romantic poetry and the human sciences of the period. Maureen McLane reveals how Romantic writers participated in a new-found consciousness of human beings as a species, by analysing their work in relation to major discourses on moral philosophy, political economy, and the emerging discipline of anthropology. The book offers original readings of canonical works, including Wordsworth's Lyrical Ballads, Mary Shelley's Frankenstein, and Percy Shelley's Prometheus Unbound, to show how the Romantics internalized and transformed ideas about the imagination, futurity, perfectibility, immortality, and population which so energized the moral and political debates of the period."--Jacket
1. Toward an anthropologic: poetry, literature, and the discourse of the species -- 2. Do rustics think?: Wordsworth, Coleridge, and the problem of a "human diction" -- 3. Literate species: populations, "humanities," and the specific failure of literature in Frankenstein -- 4. "Arithmetic of futurity": poetry, population, and the structure of the future -- 5. Dead poets and other romantic populations: immortality and its discontents -- Epilogue, or Immortality interminable: the use of poetry for life.
Includes bibliographical references (pages 268-275) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Geisteswissenschaften -- Literatur -- Englisch -- Geschichte -- 1798-1832.; English literature -- 19th century -- History and criticism; Literature and society -- Great Britain -- History -- 19th century; Literature and anthropology -- Great Britain -- History -- 19th century; Social sciences -- Great Britain -- History -- 19th century; Social problems in literature; Romanticism -- Great Britain; Population in literature; Littérature anglaise -- 19e siècle -- Histoire et critique; Littérature et société -- Grande-Bretagne -- Histoire -- 19e siècle.; Littérature et anthropologie -- Grande-Bretagne -- Histoire -- 19e siècle.; Sciences sociales -- Grande-Bretagne -- Histoire -- 19e siècle.; Problèmes sociaux dans la littérature.; Romantisme -- Grande-Bretagne.; Population dans la littérature.; POETRY -- English, Irish, Scottish, Welsh; English literature; Literature and anthropology; Literature and society; Population in literature; Romanticism; Social problems in literature; Social sciences; Great Britain; Humanwissenschaften; Geisteswissenschaften; Literatur; Romantik; England; Gedichten; Engels; Romantiek; Antropologie; Lyrik -- englische -- Romantik; Lyrik -- englische -- Gesellschaft -- Geschichte 19. Jh; Anthropologie -- Lyrik -- englische -- Geschichte 19. Jh; Lyrik -- englische -- Anthropologie -- Geschichte 19. Jh; Literatur -- Englisch -- Menschenbild -- Geschichte -- 1798-1832.; 1800-1899; Electronic books; Criticism, interpretation, etc; History